2019
DOI: 10.1021/acs.orglett.8b04042
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Heterologous Biosynthesis of the Burnettramic Acids: Rare PKS-NRPS-Derived Bolaamphiphilic Pyrrolizidinediones from an Australian Fungus, Aspergillus burnettii

Abstract: The burnettramic acids are a new class of antibiotics from an Australian fungus Aspergillus burnettii. The rare bolaamphiphilic scaffold consists of β-D-mannose linked to a pyrrolizidinedione unit via a 26-carbon chain. The most abundant metabolite displayed potent in vitro antifungal activity. Comparative genomics identified the hybrid PKS-NRPS bua gene cluster, which was verified by heterologous pathway reconstitution in Aspergillus nidulans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 36 publications
(60 reference statements)
3
67
0
Order By: Relevance
“…Alliacei species and not in any other species of sect. Flavi ( Goetz et al., 1985 , Liesch et al., 1985 , Liesch et al., 1988 , Mandelare et al., 2018 , Frisvad et al., 2019 , Li et al., 2019a , Morishita et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Alliacei species and not in any other species of sect. Flavi ( Goetz et al., 1985 , Liesch et al., 1985 , Liesch et al., 1988 , Mandelare et al., 2018 , Frisvad et al., 2019 , Li et al., 2019a , Morishita et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The tetramic acid skeleton is also found in other hybrid NPs such as equisetin, of which hybrids form other clades in the phylogeny (Clade Ib). The ME search focusing on these hybrids resulted in identification of seven hypothetical NP clades: burnettramic acid (characterized hybrid: BuaA 38 , 39 , number of hybrids: 24), Sch210972 (TasS 40 , 20), equisetin (EqxS 41 , 50), fusaridione (FsdS 41 , 5), Ib-α (25), Ib-β (12), and Ib-γ (16) (Schemes 4 and S3 , Tables S3 and S6 ). Hybrid NPs classified in this clade have unique polyketide side chains or moieties on the common tetramic acid moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that structurally related epicoccamides have only one hydroxyl group at the terminal position of the polyketide chain (Scheme S3), P450 might be responsible for the hydroxylation. Extended ME analysis showed that seven BGCs including that for burnettramic acid A possess a putative glycosyltransferase, which most likely catalyzes a glycosyltransfer reaction (Scheme S3) 38 . In contrast, equisetin (Ib-C) has a decalin skeleton, which undergoes no additional functionalizations during biosynthesis.…”
Section: Hybrid Gene Cluster Analysis Identification Of the Pyridonementioning
confidence: 99%
“…In addition to ilicicolin H, a shunt metabolite ilicicolin J (78) was isolated with an MIC of 6.3 µ g/mL against C. albicans [66]. Heterologous expression was also employed to confirm the biosynthetic gene cluster involved in the production of the burnettramic acids A and B (79 and 80) in Aspergillus burnettii FRR 5400 [67]. Burnettramic acid A had an MIC value < 1 μg/mL against C. albicans while burnettramic acid B was slightly less active with values of 1-2 μg/mL.…”
Section: Natural Product Antifungal Leads From Fungimentioning
confidence: 99%